DINAMIKA PERJUANGAN KAUM MUSLIM DALAM MENCAPAI KEMERDEKAAN INDONESIA - Murdi, Lalu; Hadi, Muhammad Shulhan (FAJAR HISTORIA: Jurnal Ilmu Sejarah dan Pendidikan, 2018)
This study deals with the dynamics of the struggle of the Muslims to achieve independence both de jure and de facto since the Japanese occupation until after the independence revolution. The method used is historical methods ranging from heuristics, criticism, interpretation and historiography. The documents used range from books, printed and online journal articles. The results of the study show that there are several criteria for the struggle of Muslim believers in Indonesia, namely: first, political struggle. In this case Islamic organizations and Islamic leaders sought to obtain such independence by means of constitutions and organizations that were legalized by the Dutch, such as MIAI which was replaced with Masyumi, social-religious organizations such as Muhammadiyah, NU, Persis and others. Meanwhile in the independence preparation institutions they participated as members of the BPUPKI and formulated the basis for an independent Indonesia. Second, the struggle for state ideology. In this case the Muslims fight for the foundation of the state is Islamic law, and they are not dealing with the Japanese but the national group. The difference between them revolves around the separation of religion from the country which is fought by national groups, whereas Islamic groups fight for Islam as the basis of the state. Third, resistance with rebuke, for example, the Japanese act of implementing the seikere tradition was not only opposed by the NU, but also other Islamic leaders.